Análise de práticas do mecanismo de controle da governança na implementação de políticas da saúde: estudo de casos em municípios brasileiros - Borges, Andreia Couto (2024)
The high decentralization of actions and services relating to the public health system in the country encompasses organizational principles of shared responsibility between the three levels of government, with the aim that these interventions are offered with higher quality, and grants municipalities greater participation as executors of policies and recipients of federal financial resources. It is essential that these municipalities have technical, managerial, administrative and financial conditions, further intensifying popular participation as a great value in control and supervision through the Health Councils, in accordance with the Federal Constitution of 1988 (CF/88). However, transfers of federal resources to entities have presented problems in the implementation of public policies, resulting from the omission of accountability, contrary to the provisions of article 70, sole paragraph of CF/88, as well as accountability inadequate. In this sense, given the complexity in monitoring, controlling and supervising the transfers of federal health resources to the Federation units, the following question was proposed: What governance practices are most needed to avoid the return of public resources? Of health? The general objective established was to analyze practices of the public governance control mechanism most lacking in the application of federal 24h UPA resources, referring to 15 municipalities with a population above 50 thousand inhabitants, considering the Ordinance on the return of resources GM/MS No. 4,277 from 12/06/2022. The specific objectives include: verifying the transparency of municipalities from the perspective of compliance with the provisions of the Access to Information Law (LAI); and furthermore, verify the transparency culture of the municipalities regarding the Annual Management Report (RAG) and Quarterly Detailed Report (RDQ), from 2018 to 2022. In addition to identifying weaknesses and limitations regarding the promotion of transparency in the main system for monitoring works of transfers in the fund-to-fund modality (SISMOB) and accountability by municipal entities from the perspective of horizontal accountability. Verify the actions from the perspective of vertical accountability (social control) during the municipal qualification process and the limitations encountered in monitoring and monitoring the works, considering the available mechanisms. And identify possible guidelines and practices that contribute to the monitoring and good application of federal health resources at the municipal level. The methodology refers to research of an applied nature, with a qualitative approach and, regarding the technical procedure, it is a multiple case study in which 15 Brazilian municipalities, with a population above 50 thousand inhabitants, had to return health resources to the federal government. The main result points to the need to better promote transparency and ensure the accountability of federal resources, with the availability of updated information to monitor works. The limitations refer to the lack of availability of the RAG, via the SAGE portal, for the years in which the canceled proposals were qualified. It is expected to strengthen the system for monitoring the application of resources, integrated with all SUS governance instances.